Multiple cystic echinococcosis in abdominal and pelvic cavity treated by surgery with a 4-year follow-up: a case report - Yan, Lerong; Chu, Zhiqiang; Yang, Jian; Zhang, Yongguo; Liu, Guisheng; Lei, Zhen; Chen, Qian; Li, Jiang; Yang, Jing; Zhao, Meifeng; Zhang, Shijie; Wu, Xiangwei; et al. (Frontiers in Medicine, 2024)
We report a case of a male patient who presented with multiple abdominal and pelvic echinococcosis. The patient had been diagnosed with hepatic echinococcosis for 7 years and developed intermittent distension and discomfort in the upper abdomen after an accidental fall. In recent years, the patient’s abdominal distention increased gradually. Computed tomography revealed multiple hydatid cysts in the liver, spleen, abdominal cavity, and pelvic cavity. Abdominal organs were severely compressed, such that he could not eat normally except for a liquid diet. The patient underwent radical surgical resection based on the multi-disciplinary treatment (MDT) and the operation lasted 10 h, nearly 100 hydatid cysts were excised, about 18 liters of cyst fluid and cyst contents were removed, and the patient lost 20 kg of weight after surgery. The operation was successful, but there were still some postoperative complications such as hypovolemic shock, postoperative ascites, postoperative bile leakage. Treatment measures for the patient were anti-infection, antishock, clamping the abdominal drainage tube, and negative pressure abdominal puncture drainage. At follow up the patient’s quality of life had been significantly improved with 15 kg weight gain compared to before.